2018
DOI: 10.1126/scisignal.aat0138
|View full text |Cite
|
Sign up to set email alerts
|

The receptor tyrosine kinase HIR-1 coordinates HIF-independent responses to hypoxia and extracellular matrix injury

Abstract: Inadequate tissue oxygen, or hypoxia, is a central concept in the pathophysiology of ischemic disorders and cancer. Hypoxia promotes extracellular matrix (ECM) remodeling, cellular metabolic adaptation, and cancer cell metastasis. To discover new pathways through which cells respond to hypoxia, we performed a large-scale forward genetic screen in Caenorhabditis elegans and identified a previously uncharacterized receptor tyrosine kinase named HIR-1. Loss of function in hir-1 phenocopied the impaired ECM integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 73 publications
4
21
0
1
Order By: Relevance
“…Collectively these data show that nhr-49 is a core part of a hypoxia response pathway that is independent of hif-1 signalling. In support of our study, a recent publication (Vozdek et al, 2018) showed that nhr-49 is required to induce the hif-1-independent hypoxia response gene comt-5 both in 0.5% O2 and in a strain mutant for the kinase hir-1. In hypoxia, HIR-1 coordinates remodeling of the extracellular matrix independently of HIF-1 (Vozdek et al, 2018).…”
Section: Nhr-49 Controls a Novel Hypoxia Response Pathway That Is Parsupporting
confidence: 89%
See 3 more Smart Citations
“…Collectively these data show that nhr-49 is a core part of a hypoxia response pathway that is independent of hif-1 signalling. In support of our study, a recent publication (Vozdek et al, 2018) showed that nhr-49 is required to induce the hif-1-independent hypoxia response gene comt-5 both in 0.5% O2 and in a strain mutant for the kinase hir-1. In hypoxia, HIR-1 coordinates remodeling of the extracellular matrix independently of HIF-1 (Vozdek et al, 2018).…”
Section: Nhr-49 Controls a Novel Hypoxia Response Pathway That Is Parsupporting
confidence: 89%
“…In support of our study, a recent publication (Vozdek et al, 2018) showed that nhr-49 is required to induce the hif-1-independent hypoxia response gene comt-5 both in 0.5% O2 and in a strain mutant for the kinase hir-1. In hypoxia, HIR-1 coordinates remodeling of the extracellular matrix independently of HIF-1 (Vozdek et al, 2018). Thus, although our RNA-seq results did not identify comt-5 as a target of NHR-49 in hypoxia, this study supports the idea of a hif-1independent hypoxia response pathway involving nhr-49.…”
Section: Nhr-49 Controls a Novel Hypoxia Response Pathway That Is Parsupporting
confidence: 89%
See 2 more Smart Citations
“…Currently, we do not know the alteration in cellular behavior that hypoxia triggers to render cells less responsive to YM155. Although HIFs represent the best-studied mechanism by which hypoxia impacts cellular responses through gene regulation, many reports confirm the critical roles of HIF-independent cellular responses to hypoxia ( Vozdek et al., 2018 ; Fortenbery et al., 2018 ; Ahmed et al., 2018 ; Park et al., 2016 ). Importantly, a recent study provided strong evidence that hypoxia re-programs global changes in gene expression by rapidly modifying chromatin methylation through a HIF-independent mechanism ( Batie et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%